2016
DOI: 10.5812/atr.37070
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Chest Computed Tomography in Patients with Rib Fractures CT Chest and Rib Fractures

Abstract: BackgroundChest CT is more sensitive than a chest X-ray (CXR) in diagnosing rib fractures; however, the clinical significance of these fractures remains unclear.ObjectivesThe purpose of this study was to determine the added diagnostic use of chest CT performed after CXR in patients with either known or suspected rib fractures secondary to blunt trauma.MethodsRetrospective cohort study of blunt trauma patients with rib fractures at a level I trauma center that had both a CXR and a CT chest. The CT finding of ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 18 publications
0
37
1
Order By: Relevance
“…However, in their study the diagnosis of rib fractures did not result in differences of the length of hospital stay, intensive care unit (ICU) admission rate or in-hospital mortality, which was remarkably higher-by 10.3%-in patients with CT-detected rib fractures [10]. Further studies on blunt trauma patients of every age have demonstrated that chest XR misses rib fractures and relevant intrathoracic injuries in blunt trauma patients of every age [27][28][29]. The proportion of undiagnosed rib fractures in chest XR ranges from 45% [29] to 74.5% (median three additional fractures in CT) [27].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, in their study the diagnosis of rib fractures did not result in differences of the length of hospital stay, intensive care unit (ICU) admission rate or in-hospital mortality, which was remarkably higher-by 10.3%-in patients with CT-detected rib fractures [10]. Further studies on blunt trauma patients of every age have demonstrated that chest XR misses rib fractures and relevant intrathoracic injuries in blunt trauma patients of every age [27][28][29]. The proportion of undiagnosed rib fractures in chest XR ranges from 45% [29] to 74.5% (median three additional fractures in CT) [27].…”
Section: Discussionmentioning
confidence: 87%
“…Further studies on blunt trauma patients of every age have demonstrated that chest XR misses rib fractures and relevant intrathoracic injuries in blunt trauma patients of every age [27][28][29]. The proportion of undiagnosed rib fractures in chest XR ranges from 45% [29] to 74.5% (median three additional fractures in CT) [27]. Intrathoracic injuries have been CT-identified in 26% of the cases [28], leading to changes in clinical management in 8% [28], respectively 34.5% [27] of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracic CT imaging is superior to chest radiography. Approximately 75% of all rib fractures which are seen on chest CT are missed on radiography [36,37]. The low sensitivity is aggravated in the trauma setting because chest radiography is performed with the patient in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chapman et al (24) noted that plain films missed about 75% of fractures diagnosed by CT; this led to changes in clinical management in 35% of patients. Other studies have found similar results (25,26).…”
Section: Indications For Surgerymentioning
confidence: 99%